FINANCIAL PERFORMANCE ANALYSIS OF SOE AND FOREIGN CAPITAL CEMENT COMPANIES IN INDONESIA - Malik, Ahmad Dahlan; Handono, Wahyu Agung (PEOPLE: International Journal of Social Sciences, 2019)
In order to achieve the Master Plan for the Acceleration and Expansion of the Indonesian Economic Development (MP3EI) program that has a significant impact on cement demand outside java, it is necessary to improve the performance of cement companies, especially state-owned (SOE) and Foreign Investment (PMA) cement companies in Indonesia. Their performance are analyzed along with the selection of independent variables in the discrimination function as a variable that explains precisely the performance of the company based on the Discriminant Stepwise Method. This research is analyzed by Du Pont System Analysis where both SOE and PMA have a good value of the performance; Financial Ratios where all of the companies have positive value with different trends; The Decree of the Minister of Finance of the Republic of Indonesia No. 826/KMK.013/1992 indicating that healthy company performance only owned by Semen Batu Raja and Indocement; Decree of the Minister of BUMN No: KEP-100/MBU/2002 in financial aspects having AA predicate healthy companies owned by Semen Indonesia, Indocement, and Siam Cement while the rest are having below AA grade; Economic Value Added (EVA) having no economic value by Semen Batu Raja and Ultratech while the other have positive EVA; Tobin’s q indicating that only Holcim and Anhui Conch companies having average value while the others having overvalued; and Altman Z-Score of SOE and PMA having value above 2.9 explaining the companies do not have the bankrupt condition. Meanwhile the data of those analysis is in the period 2013-2016.